2009
DOI: 10.1073/pnas.0807760106
|View full text |Cite
|
Sign up to set email alerts
|

agr receptor mutants reveal distinct modes of inhibition by staphylococcal autoinducing peptides

Abstract: Through the agr quorum-sensing system, staphylococci secrete unique autoinducing peptides (AIPs) and detect their concentration via the AgrC transmembrane receptor, coordinating local bacterial population density with global changes in gene expression. Unique AIP and AgrC variants exist within and between species, and although autologous interactions lead to agr activation, heterologous interactions usually lead to cross-inhibition, resulting in natural quorum-sensing interference. To gain insight into the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
115
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 28 publications
4
115
1
3
Order By: Relevance
“…In terms of altered, rather than broadened, specificity mutants, to achieve a change in Tar specificity, 4 to 12 simultaneous point mutations were required (40). In AgrC, either multiple mutations or exchanges of significant portions of transmembrane domains were required (39,41,42). This is not the case in CqsS, because we can change any one of five amino acids (W104, S107, F162, F166, and C170) and alter the receptor specificity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of altered, rather than broadened, specificity mutants, to achieve a change in Tar specificity, 4 to 12 simultaneous point mutations were required (40). In AgrC, either multiple mutations or exchanges of significant portions of transmembrane domains were required (39,41,42). This is not the case in CqsS, because we can change any one of five amino acids (W104, S107, F162, F166, and C170) and alter the receptor specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, this powerful approach, to our knowledge, has not been routinely adapted for studying prokaryotic two-component signal-transduction systems. The present work, together with the elegant studies on the Agr system by Muir, Novick, and coworkers (39,41,52), suggests that rationally designed ligands can be exploited to study and ultimately to control two-component histidine kinase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geisinger et al recently examined inhibition of constitutively active AgrC mutants by a range of AIP analogues and found that heterologous AIPs can inhibit AgrC activity by distinct mechanisms. Some heterologous AIPs were competitive inhibitors of the cognate AIP, while others were found to act as inverse agonists, inducing a nonactive AgrC conformation even in the absence of activating ligand (222). This may help to explain why residues critical for activity differ between AIP groups.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…In addition, it encodes AgrD, the precursor of the quorum signal that can further be processed and exported as a thiolactone-containing oligopeptide autoinducer (autoinducing peptide, AIP) by the cotranscribed AgrB. Upon binding to the extracellular sensory domain of AgrC, AIP activates the kinase activity of AgrC, subsequently leading to phosphorylation of the response regulator AgrA (13,14). Phosphorylated AgrA regulates transcription of genes encoding metabolic factors and phenol-soluble modulin (PSM) peptides (15) and, more importantly, triggers the expression of the agr operon by binding to the promoter regions P2 (for RNAII) and P3 (for RNAIII), thereby forming an autoinduction genetic circuit to ensure a timely rearrangement of target gene expression at a certain threshold level of population density.…”
mentioning
confidence: 99%